Hubungan Regulasi Emosi Dengan Resiliensi Diri Korban Kekerasan Seksual Di Provinsi Gorontalo - Anissa Dwi Putri Said Nurkamiden Anissa; Anik Indarwati; Zulkarnain Zulkarnain (CV. Ulil Albab Corp, 2026)
The number of sexual violence cases against children continues to rise, showing a significant increase each year. This form of violence has long-lasting psychological effects and has become a complex social problem. This study aims to determine the relationship between emotion regulation and self-resilience among victims of sexual violence in Gorontalo Province. Sexual violence can lead to serious psychological impacts, such as trauma, anxiety, and depression, making emotion regulation and resilience essential factors in victims’ recovery. This research uses a quantitative approach with a correlational method. The population consists of 57 victims of sexual violence in Gorontalo Province. The sample includes 37 victims selected through purposive sampling. Data were collected using an emotion regulation scale and a resilience scale. The results of data analysis indicate a significant positive relationship between emotion regulation and self-resilience (r = 0.994; p = 0.000). This means that the higher the level of emotion regulation, the higher the level of self-resilience among victims of sexual violence.